Improvement of functional characteristics of Hypophthalmichthys molitrix protein by modification with chitosan oligosaccharide - Cong, Haihua; Wu, Qiming; Zhang, Zhuoran; Kan, Juntao (Frontiers in Nutrition, 2023)
In the food processing field, it’s very often that fish proteins are denatured affecting the nutritional value of the product which is vital to be solved. By using appropriate sugar donors for glycosylation with protein, improving the stability and emulsification properties of fish proteins can be achieved. This research looks into the impacts of enzymatic chitosan oligosaccharide (CO) at various concentration (0.15%, 0.30%, 0.45%, 0.60%, w/v) upon the molecular makeup and function of silver carp myofibrillar protein (MP) in an attempt to comprehend the impact of electrostatic binding among MP as well as CO on protein conformation . Analysis was done on the impact of various CO concentrations upon MP's secondary structure, conformational changes, and functional characteristics. Twelve sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) assays were implemented to monitor MP; Fourier transform infrared spectroscopy, endogenous fluorescence spectroscopy, and UV absorption spectra were carried out to investigate the influence of CO on MP; Particle size distribution, emulsifying activity index (EAI), solubility, turbidity, sulfhydryl content, carbonyl content, foaming capacity, surface hydrophobicity, emulsifying stability index (ESI), and foam persistence were all investigated. In addition, we used dynamic light scattering, scanning electron microscope, and atomic force microscope to analyze myosin (MO) and 0.60% CO-MO complex. The results demonstrated that CO and MP form complexes through hydrogen bonding and electrostatic interactions. CO modification not only delayed the oxidation of MP but also promoted MP to show better solubility, foaming, and foaming stability. In addition, CO modified myosin particle size decreased, reducing myosin's roughness and making myosin's structure more compact. To sum up, molecular interaction could change functional characteristics, and products with special properties could be developed after modification with chitosan oligosaccharide.